Implementation and Evaluation of Therapeutic Online Coaching Using Habit Reversal Training in Children With Tourette’s Disorder – A Pilot Study - Viefhaus, Paula; Adam, Julia; Goletz, Hildegard; Woitecki, Katrin; Döpfner, Manfred (Frontiers in Psychology, 2021)
Cognitive-behavioral interventions can be difficult to implement in daily routine, which is often essential for generalizing treatment effects to natural settings. Furthermore, there is a lack of adequate care options concerning habit reversal training for children with Tourette’s disorder. The objective of this study is to evaluate therapeutic online coaching via videoconferencing in the natural environment of children with Tourette’s disorder in addition to face-to-face therapy (blended therapy). Online coaching took place twice a week for a maximum of 12 weeks. In a single-case study (n = 5; patients aged 8-11 years; clinical trial registry number: DRKS00017199), the first results were obtained for exploratory purposes, especially with regard to the feasibility and reduction of symptoms and impairment. Various outcome measures were assessed (severity of symptoms, impairment, practical implementation and satisfaction). Despite some principal limitations, the findings provide first hints that blended therapy is feasible and improves symptoms in some children with tics.